Internet Use and Global Activism at the United States Social Forum - Schwarz, Elizabeth Anne Gervais (AoIR Selected Papers of Internet Research, 2013)
Scholars maintain that the global reach of the internet encourages global connectedness and global activism. Using survey data from the 2010 United States Social Forum, this study extends research exploring internet use and transnational social movement activity by examining activists’ use of four different internet technologies. The study examines how the use of communication, online social networking, collaboration, and multimedia sharing technologies relate to whether activists have a high level of international contact, believe they are part of a global social movement, and are affiliated with international movements. The results reveal that use of the four types of internet tools do not relate to global activism. Examining the intensity of internet use, the use of more types of online tools is related to high levels of international contact. The findings suggest that activists do use multiple internet technologies to maintain their networks with other activists around the globe.